Post-traumatic stress disorder is associated with PACAP and the PAC1 receptor - Ressler, Kerry J.; Mercer, Kristina B.; Bradley, Bekh; Jovanovic, Tanja; Mahan, Amy; Kerley, Kimberly; Norrholm, Seth D.; Kilaru, Varun; Smith, Alicia K.; Myers, Amanda J.; Ramirez, Manuel; Engel, Anzhelika; et al. (Nature (London), 2011)
Pituitary adenylate cyclase-activating polypeptide (PACAP) is known to broadly regulate the cellular stress response. In contrast, it is unclear if the PACAP–PAC1 receptor pathway has a role in human psychological stress responses, such as post-traumatic stress disorder (PTSD). Here we find, in heavily traumatized subjects, a sex-specific association of PACAP blood levels with fear physiology, PTSD diagnosis and symptoms in females. We examined 44 single nucleotide polymorphisms (SNPs) spanning the PACAP (encoded by ADCYAP1 ) and PAC1 (encoded by ADCYAP1R1 ) genes, demonstrating a sex-specific association with PTSD. A single SNP in a putative oestrogen response element within ADCYAP1R1, rs2267735, predicts PTSD diagnosis and symptoms in females only. This SNP also associates with fear discrimination and with ADCYAP1R1 messenger RNA expression in human brain. Methylation of ADCYAP1R1 in peripheral blood is also associated with PTSD. Complementing these human data, ADCYAP1R1 mRNA is induced with fear conditioning or oestrogen replacement in rodent models. These data suggest that perturbations in the PACAP–PAC1 pathway are involved in abnormal stress responses underlying PTSD. These sex-specific effects may occur via oestrogen regulation of ADCYAP1R1 . PACAP levels and ADCYAP1R1 SNPs may serve as useful biomarkers to further our mechanistic understanding of PTSD. A biomarker for stress disorders In many species, pituitary adenylate cyclase-activating polypeptide (PACAP) is implicated in physiological responses to stress. A study of a sample of highly traumatized human females now shows that PACAP blood levels correlate with a diagnosis of post-traumatic stress disorder and with the degree of fear conditioning responses. One particular single-nucleotide polymorphism in the oestrogen response element of the receptor gene is closely associated with the condition, as is increased methylation of the receptor gene. Experiments in mice subjected to fear conditioning revealed increased transcription of both PACAP and receptor genes in the amygdala. These findings may set the stage for a novel biomarker for stress disorders and for explaining known sex differences in the occurrence of such conditions.